Pengaruh Kombinasi Pijat BBLR dan KMC Terhadap Rooting-Sucking ReflexNeonatus BBLR Di RSUD Sleman Tahun 2016 - Rhomawati, Wahyu Surya; Estiwidani, Dwiana; Sujiyatini, Sujiyatini (Jurnal Kesehatan Ibu dan Anak, 2017)
Infant Mortality Rate (IMR) was one measure of the health status of a country. Various attempts were made to reduce IMR. One of the LBW problems was a weight that did not increase due rooting sucking reflex was not robust. This study was aimed determine the difference rooting sucking reflex LBW infants neonatal who did a combination of massage and KMC compared to those who do only KMC in RSUD Sleman 2016. This type of study was the experiment. The study design was a non equivalent control group. Study was conducted in RSUD Sleman on November 1 until Desember 30, 2016. The subjects were LBW neonates in hospitals who birthed on October to December 2016 that matched with criteria. The total sample in this study were 46 respondents. Data collected by form observation of rooting sucking reflex and stopwatch. Analysis of data used Man Whiteney and Wilcoxon. Bivariable analysis resulted count value z> z table and a p-value <0.05. There was a significant difference between LBW who get massage combination with KMC compared only KMC. The conclusion from this study was there were different effect LBW message combination with KMC and KMC to rooting sucking reflex neonatal LBW in RSUD Sleman 2016.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;">